A Method and System for Combining the Advantages of Gasoline Compression Ignition (GCI) Engine Technologies into Hybrid Electric Vehicles (HEVs) - Hyun Woo WON (MDPI AG, 2021)
By combining a clean fuel such as gasoline with a high efficiency thermodynamic cycle (compression ignition), it is possible to demonstrate a powertrain that is clean and efficient, thus breaking the historical trade-off between decreasing CO2 and reducing criteria pollutants. The gasoline compression ignition (GCI) engine is a promising technology that can be used to improve thermal efficiency while reducing emissions. Its low temperature combustion does however lead to several problems that need to be overcome. The present study relates to a method and system for combining the advantages of GCI engine technology into a hybrid electric vehicle (HEV) to maximize the benefits. A plausible path is to operate the GCI engine at conditions where the benefits of a GCI engine could be maximized and where an electric motor can supplement the conditions where the GCI is less beneficial. In this study, GCI engines with different cetane number (CN) fuels were selected, and a hybrid simulation tool was used to address the potential of the GCI engines into hybrid electric vehicles. Co-developments can demonstrate efficiency and emission solutions through the achievements of the study, which will address examples of the competitive powertrain and will introduce more than 30% of CO2 reduction vehicle by 2030.